Analisis Faktor-faktor yang Mempengaruhi Stock Split dan Pengaruhnya terhadap Nilai Perusahaan - Widiastuti, Harjanti; Usmara, Usmara (Universitas Muhammadiyah Yogyakarta, Indonesia, 2005)
This study aimed to get empirical evidence about the factors that affect stock split and its influence on the value of companies listed on the Jakarta Stock Exchange. Factors influencing stock split in this study consisted of the Price to Earning Ratio (PER), Price to Book Value (PBV), and the bid-ask spread. Sample consisted of 30 non-financial companies that do stock split and 30 non-financial companies that do not do a stock split in 2000-2001. Based on the analysis in the previous chapter can be concluded first, the results of statistical tests to logit regression analysis showed that the level of expensiveness stock prices as measured by PBV significant positive effect on the company's decision to conduct a stock split. However, this study failed to show that the level of expensiveness stock prices as measured by PER is a variable that significant positive effect on the company's decision to conduct a stock split.